Simulation Study Of Transmission Electron Microscopy Imaging Of Graphene Stacking - Nelson, F; Diebold, A C; Hull, R (2009 International Conference on Frontiers of Characterization and Metrology for Nanoelectronics, 2009)
Graphene is the subject of intense study due to its high mobility and mechanical integrity. These properties make it an attractive material for the 'beyond CMOS'technology that will replace today's transistor. Acceleration of process and device technology requires considerable advances in the imaging and characterization of graphene. The physical dimensions of available single and multi-layer samples are not large enough for many metrology methods. For example, the spot size of ellipsometry is typically larger than available samples. Electron microscopy of graphene is also challenging. Carbon is a difficult element to image with electron microscopy because of its low atomic number. The high mobility of single layer and misoriented two and three layer graphene make it attractive for nanoelectronics. The current investigation explores HRTEM simulations of graphene stacking configurations AAA/ABA/ABC as well as bilayers with misorientations between the individual layers. HAADF (High Angle Annular Dark Field) STEM simulation is also discussed. Images calculated using the Multislice algorithm show discernable differences between the stacking sequences when simulated in the presence of random noise.